Uji Efektifitas Berbagai Konsentrasi Ekstrak Daun Tanaman Terhadap Penekanan Populasi Nematoda Puru Akar (Meloidogyne spp.) dalam Tanah, Akar, dan Produksi Tanaman Tomat (Lycopersicum esculentum Mill.) - NI MADE PUTRI YUDANTARI; MADE SRITAMIN; I DEWA PUTU SINGARSA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Test the Effectiveness of Various Concentrations of Plant Leaf Extracts Against Root Knot Nematode Suppression (Meloidogyne spp.) In Soil, Roots, and Production Tomato Plants (Lycopersicum esculentum Mill.). Root knot disease is a disease caused by root knot nematodes Meloidogyne spp. Nematodes grown on the roots of plants by inhibiting nutrients that interfere with the process of photosynthesis and stunted plants showing symptoms, while wilting, and permanent wilting on the plant at ground level. While the plants in the basement there is a knot at the root. In this study to control root knot Meloidogyne spp. using sirih (Piper betle Linn.), kirinyuh (Chomolaena odorata Linn.), and tembelekan (Lantana camara Linn.) with a concentration of 100 cc/polybag, 200 cc/polybag, and 300 cc/ polybag of each extract solution leaves the test.The results of the calculation of the population of nematodes per 300 g soil showed sirih extract suppressed the population of root knot nematodes Meloidogyne spp. the good, 23 pcs/??300 g soil, with an emphasis percentage of 95.4%, next is to extract kirinyuh 26 psc/300 g soil (94.7%), and extract tembelekan 27 psc/300 g soil (94.4 %). In the calculation of the population of root knot nematodes Meloidogyne spp. per 1 g of roots, extract of piper betle was the most good in suppressing root knot nematode populations, there are only 22 pcs/1 g roots, with a percentage of 95.5%, followed by extracts of kirinyuh 24 pcs/1 g roots (95.1%) , and extract of tembelekan 28 psc/1 g roots (94.3%). Keywords: Chromolaena odorata Linn., Lantana camara Linn., Lycpersicum esculentum Mill., Piper betle Linn..